Intermediary balance sheets and the treasury yield curve - Du, Wenxin; Hébert, Benjamin; Li, Wenhao (Journal of Financial Economics, 2023)
We document a regime change in the Treasury market post-Global Financial Crisis (GFC): dealers switched from net short to net long Treasury bonds. We construct “net-long” and “net-short” curves that account for balance sheet and financing costs, and show that actual yields moved from the net short curve pre-GFC to the net long curve post-GFC. Our theory shows the regime shift caused negative swap spreads and co-movement among swap spreads, dealer positions, and covered-interest-parity violations. Furthermore, the effects of various monetary and regulatory policies are regime-dependent. We highlight Treasury supply as a plausible driver of this regime shift.